2017
DOI: 10.1016/j.mri.2016.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional black-blood T 2 mapping with compressed sensing and data-driven parallel imaging in the carotid artery

Abstract: This study demonstrates the feasibility of combining CS and PI for accelerating 3D T mapping in the carotid artery, with accurate T measurements and good repeatability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Makhijani et al used a hidden Markov tree model based compressing method for carotid plaque imaging using a diffusion prepared gradient echo sequence (MERGE), and found that a 4.5-fold acceleration achieved imaging quality comparable to a fully sampled reference in 6 patients with carotid diseases [16], which is comparable with the optimized acceleration factor in this study (fivefold). Yuan et al investigated a compressed sensing based 3D multi-contrast fast-spin-echo imaging of the carotid plaque in 12 volunteers and 8 patients [18]. The sequence they used (CUBE) is comparable with the sequence in this study (SPACE).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Makhijani et al used a hidden Markov tree model based compressing method for carotid plaque imaging using a diffusion prepared gradient echo sequence (MERGE), and found that a 4.5-fold acceleration achieved imaging quality comparable to a fully sampled reference in 6 patients with carotid diseases [16], which is comparable with the optimized acceleration factor in this study (fivefold). Yuan et al investigated a compressed sensing based 3D multi-contrast fast-spin-echo imaging of the carotid plaque in 12 volunteers and 8 patients [18]. The sequence they used (CUBE) is comparable with the sequence in this study (SPACE).…”
Section: Discussionmentioning
confidence: 91%
“…Previous compressed sensing vessel wall studies have focused on carotid plaque imaging, including plaque morphology imaging using 3D gradient echo sequences with black blood preparation [16] or 3D fast spin echo sequences (CUBE) [20] and T2 mapping [18]. Makhijani et al used a hidden Markov tree model based compressing method for carotid plaque imaging using a diffusion prepared gradient echo sequence (MERGE), and found that a 4.5-fold acceleration achieved imaging quality comparable to a fully sampled reference in 6 patients with carotid diseases [16], which is comparable with the optimized acceleration factor in this study (fivefold).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, motion detection with reconstruction of corrupted data was developed for the conventional Cartesian MESE acquisition, but further modifications to the acquisition offer interesting possibilities. Compressed sensing could be applied to modified k‐space trajectories, for example, radial sampling, that could be intrinsically more robust to motion . Using randomized phase‐encoding within an echo train could allow T 2 mapping from undersampled data .…”
Section: Discussionmentioning
confidence: 99%
“…A small number of studies have featured CS in the evaluation of carotid VWI [17][18][19][20], but the numbers of subjects in those preliminary papers were around 10 patients, and results were not conclusive. The purpose of this study was to compare the visualization of plaques and vessel walls of the internal carotid artery (ICA) between 3D T1-FSE imaging with conventional SPACE and with a prototype CS-SPACE in a larger number of cases.…”
Section: Sensing T1-space Introductionmentioning
confidence: 99%